2019
DOI: 10.1007/s13300-019-00692-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Liraglutide on Times in Glycaemic Ranges as Assessed by CGM for Type 2 Diabetes Patients Treated With Multiple Daily Insulin Injections

Abstract: IntroductionThe effects of the GLP-1 analogue liraglutide on time in hypoglycaemia, time in hyperglycaemia, and time in range for type 2 diabetes patients initially treated with multiple daily insulin injections (MDI) were investigated. Variables associated with hypoglycaemia in the current population were also identified.MethodsAnalyses were based on data from a previously performed double-blind, placebo-controlled trial in which 124 MDI-treated patients with type 2 diabetes were randomized to liraglutide or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…Similar to our results, the MDI Liraglutide trial 22 found that reductions in mean glucose levels and standard deviation estimated by masked continuous glucose monitoring were significantly greater in the liraglutide group than in the placebo group (−1.9 and −0.5 mmol/L (−34.2 and −9 mg/dL), respectively; P<0.001). The study of Lind et al 23 showed that liraglutide treatment lowers glucose levels and reduces time in hypoglycemia in T2DM patients treated with MDI.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our results, the MDI Liraglutide trial 22 found that reductions in mean glucose levels and standard deviation estimated by masked continuous glucose monitoring were significantly greater in the liraglutide group than in the placebo group (−1.9 and −0.5 mmol/L (−34.2 and −9 mg/dL), respectively; P<0.001). The study of Lind et al 23 showed that liraglutide treatment lowers glucose levels and reduces time in hypoglycemia in T2DM patients treated with MDI.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, when novel glucose-lowering treatments are evaluated both in persons with type 1 and type 2 diabetes, 6,7,11,13 a certain amount of time-in-hypoglycemia registered via glucose sensor should be viewed as normal, at least for the 3.9 mmol/L cut point. However, none or very little time in hypoglycemia<3.0 mmol/L should exist where the median and mean time was 0.0% and 0.5%, respectively, in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…20,23 Earlier studies also did not use masked CGM, [21][22][23][24][25][26] which may influence glucose levels to some extent. 11,13 Others used earlier generation CGM sensors, which were generally less accurate than the Dexcom G4. 10,24 Finally, OGTT was not performed in some studies; thus, it is likely a significant number of persons with prediabetes or diabetes were included.…”
Section: Earlier Studiesmentioning
confidence: 99%
“…DM has become the third major disease threatening human health after cancer, cardiovascular, and cerebrovascular diseases (Fawzy et al, ; Xu et al, ). It is a group of clinical syndromes caused by the interaction of genetic and environmental factors (Sofizadeh et al, ) (El Husseny et al, ). The insufficient and relative lack of insulin secretion or the reduced insulin sensitivity of target tissue cells (the insulin resistance) leads to a series of nutrient metabolic disorders such as sugar, fat, protein, water, and electrolytes, resulting in hyperglycemia (Gupta et al, ).…”
Section: Discussionmentioning
confidence: 99%